Method for preparing expanded graphite with high expansion volume through activation or pretreatment
By adding activator or pretreatment of graphite sheets during the preparation of expanded graphite, the problem of insufficient expansion volume in traditional methods is solved, and the preparation effect of high expansion volume and low cost is achieved.
Patent Information
- Application Number
- CN202411718123.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The expanded graphite prepared by traditional methods has a low expansion volume and is difficult to meet the application needs of high expansion volume.
By mixing natural scale graphite, potassium permanganate, concentrated sulfuric acid and activator for oxidation intercalation reaction, expandable graphite and expand at high temperature, or by pretreatment of natural scale graphite, the sheet layer is slightly opened, reducing the amount of oxidant and intercalation agent and increasing the expansion volume.
The high expansion volume of expanded graphite is achieved, the average expansion volume reaches 400mL/g or higher, and the operation steps are simple and the cost is low, which solves the problems of high cost of traditional methods and environmental pollution.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphite materials, and in particular to a method for preparing high-expansion volume expanded graphite through activation or pretreatment. Background Art
[0002] Expanded graphite is a carbon material with high expansion volume obtained by oxidative intercalation of flake graphite. It has a loose and porous worm-like structure, good electrical and thermal conductivity, high chemical stability, and large specific surface area. It has broad application prospects in many fields.
[0003] The traditional preparation method of expanded graphite is to use chemical reagents such as concentrated sulfuric acid, potassium permanganate and hydrogen peroxide to oxidize and intercalate flake graphite to form graphite with interlayer intercalants, that is, expandable graphite. At high temperatures, the interlayer intercalants of expandable graphite are rapidly vaporized by high heat, and the formed gas will produce huge tension on the graphite sheets, causing the graphite sheets to open up and form expanded graphite.
[0004] At present, the expansion volume of expanded graphite prepared by traditional methods is relatively low. Summary of the invention
[0005] In view of this, the present invention provides a method for preparing expanded graphite with high expansion volume by activation or pretreatment. The expanded graphite prepared by the method provided by the present invention has high expansion volume, simple operation steps and low cost.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A method for preparing high expansion volume expanded graphite by activation comprises the following steps:
[0008] Natural flake graphite, potassium permanganate, concentrated sulfuric acid and an activator are mixed to perform an oxidation intercalation reaction to obtain expandable graphite; the activator is phosphoric acid, phosphate or an organic solvent; the organic solvent is one or more of carboxylic acid and alcohol;
[0009] The expandable graphite is expanded at high temperature to obtain the high expansion volume expanded graphite; the temperature of the high temperature expansion is 800-900°C.
[0010] Preferably, the mass ratio of the natural flake graphite to potassium permanganate is 1:(0.08-0.4); the dosage ratio of the natural flake graphite to concentrated sulfuric acid is 1g:(2-6)mL; when the activator is phosphoric acid or an organic solvent, the dosage ratio of the natural flake graphite to the activator is 1g:(0.5-2)mL; when the activator is a phosphate, the mass ratio of the natural flake graphite to the activator is 1:(1-4);
[0011] The concentration of the phosphoric acid is 83-88 wt %; the carboxylic acid is formic acid and / or acetic acid; the alcohol is ethanol; and the phosphate is dihydrogen phosphate.
[0012] Preferably, the mixing of natural flake graphite, potassium permanganate, concentrated sulfuric acid and an activator comprises: firstly mixing natural flake graphite and potassium permanganate and heating them to 73-75° C., and then adding concentrated sulfuric acid and an activator;
[0013] The temperature of the oxidation intercalation reaction is 75-80° C., and the reaction time is 10-60 minutes.
[0014] Preferably, after the oxidation intercalation reaction, the obtained reaction solution is washed with water until the pH value is 3-7, and then filtered and dried to obtain the expandable graphite; the drying temperature is 40-80° C. and the time is 2-5 hours.
[0015] Preferably, the high temperature expansion time is 3 to 5 seconds.
[0016] The present invention also provides a method for preparing high expansion volume expanded graphite by pretreatment, comprising the following steps:
[0017] The natural flake graphite is immersed in a pretreatment agent for pretreatment to obtain pretreated natural flake graphite; the pretreatment agent is phosphoric acid, phosphate solution, hot water or an organic solvent; the temperature of the hot water is 60 to 90° C.; the organic solvent is a carboxylic acid or an alcohol;
[0018] The pretreated natural flake graphite, potassium permanganate and concentrated sulfuric acid are mixed to perform an oxidative intercalation reaction to obtain expandable graphite;
[0019] The expandable graphite is expanded at high temperature to obtain the high expansion volume expanded graphite; the temperature of the high temperature expansion is 800-900°C.
[0020] Preferably, the pretreatment time is 1 to 4 hours.
[0021] Preferably, the mass ratio of the natural flake graphite to potassium permanganate is 1:(0.03-0.1); the dosage ratio of the natural flake graphite to concentrated sulfuric acid is 1g:(1.5-4)mL;
[0022] The concentration of the phosphoric acid is 83-88 wt %; the concentration of the phosphate solution is 0.375-0.425 g / mL; the carboxylic acid is formic acid and / or acetic acid; the alcohol is ethanol; and the phosphate is dihydrogen phosphate.
[0023] Preferably, after the oxidation intercalation reaction, the obtained reaction solution is washed with water until the pH value is 3-7, and then filtered and dried to obtain the expandable graphite; the drying temperature is 40-80° C. and the time is 2-5 hours.
[0024] Preferably, the high temperature expansion time is 3 to 5 seconds.
[0025] The present invention provides a method for preparing high expansion volume expanded graphite by activation, comprising the following steps: mixing natural flake graphite, potassium permanganate, concentrated sulfuric acid and an activator for oxidation intercalation reaction to obtain expandable graphite; the activator is phosphoric acid, phosphate or organic solvent; the organic solvent is one or more of carboxylic acid and alcohol; the expandable graphite is subjected to high temperature expansion to obtain the high expansion volume expanded graphite; the temperature of the high temperature expansion is 800-900°C. The present invention adds an activator to the intercalation agent, utilizes the swelling effect of the activator, makes the graphite sheet open more fully in the oxidation intercalation stage, and the intercalation agent enters more. At the same time, in the high temperature expansion stage, the activator can protect the graphite carbon layer and reduce the loss of carbon at high temperature, thereby increasing the impact of the decomposition and gasification of the intercalation agent on the sheet layer, and preparing the expanded graphite with increased expansion volume. The results of the embodiment show that the average expansion volume of the expanded graphite obtained by the method reaches 400mL / g.
[0026] The present invention also provides a method for preparing high expansion volume expanded graphite by pretreatment, comprising the following steps: soaking natural flake graphite in a pretreatment agent for pretreatment to obtain pretreated natural flake graphite; the pretreatment agent is phosphoric acid, phosphate solution, hot water or organic solvent; the temperature of the hot water is 60-90°C; the organic solvent is carboxylic acid or alcohol; the pretreated natural flake graphite, potassium permanganate and concentrated sulfuric acid are mixed for oxidation intercalation reaction to obtain expandable graphite; the expandable graphite is subjected to high temperature expansion to obtain the high expansion volume expanded graphite; the temperature of the high temperature expansion is 800-900°C. The present invention uses a pretreatment agent with swelling effect to pretreat natural flake graphite, so that the flakes are opened, and then a subsequent oxidation intercalation reaction is carried out. By using this method, on the basis of reducing the amount of oxidant and intercalation agent used, expanded graphite with significantly increased expansion volume can be prepared. The average expansion volume of the expanded graphite obtained by this method reaches 450mL / g, and the expansion effect is more significant. In addition, the pretreatment agent used in the method can be hot water, which is inexpensive and can be recycled after use, thus solving the problem of high cost and easy environmental pollution of the traditional preparation method. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 XRD spectra of the expanded graphite prepared in Comparative Example 1 and the commercially available expanded graphite in Comparative Example 2;
[0028] Figure 2 This is the SEM image of the expanded graphite prepared in Comparative Example 1;
[0029] Figure 3 This is the SEM image of the expanded graphite prepared in Example 3;
[0030] Figure 4 This is a SEM image of the expanded graphite prepared in Example 10;
[0031] Figure 5 This is a SEM image of commercially available expanded graphite. DETAILED DESCRIPTION
[0032] The present invention provides a method for preparing high expansion volume expanded graphite by activation (referred to as activation method), comprising the following steps:
[0033] Natural flake graphite, potassium permanganate, concentrated sulfuric acid and an activator are mixed to perform an oxidation intercalation reaction to obtain expandable graphite; the activator is phosphoric acid, phosphate or an organic solvent; the organic solvent is one or more of carboxylic acid and alcohol;
[0034] The expandable graphite is expanded at high temperature to obtain the high expansion volume expanded graphite; the temperature of the high temperature expansion is 800-900°C.
[0035] The present invention mixes natural flake graphite, potassium permanganate, concentrated sulfuric acid and an activator for oxidation intercalation reaction to obtain expandable graphite. In the present invention, the mass ratio of the natural flake graphite and potassium permanganate is preferably 1: (0.08-0.4), more preferably 1: (0.08-0.2); the dosage ratio of the natural flake graphite and concentrated sulfuric acid is preferably 1g: (2-6) mL, more preferably 1g: (3-5) mL; the concentration of the concentrated sulfuric acid is specifically 98wt%; in the present invention, the potassium permanganate is an oxidant, and the concentrated sulfuric acid is an intercalation agent.
[0036] In the present invention, the activator is phosphoric acid, phosphate or an organic solvent; the organic solvent is one or more of carboxylic acid and alcohol; the concentration of the phosphoric acid is preferably 83-88wt%, more preferably 85wt%; the phosphate is dihydrogen phosphate, more preferably sodium dihydrogen phosphate; the carboxylic acid is preferably formic acid and / or acetic acid; the alcohol is preferably ethanol; in a specific embodiment of the present invention, the activator is most preferably phosphoric acid; when the activator is phosphoric acid or an organic solvent, the dosage ratio of the natural flake graphite and the activator is preferably 1g:(0.5-2)mL, more preferably 1g:(1-1.5)mL; when the activator is phosphate, the mass ratio of the natural flake graphite and the activator is 1:(1-4), preferably 1:(2-3).
[0037] In the present invention, the mixing of natural flake graphite, potassium permanganate, concentrated sulfuric acid and an activator preferably comprises: firstly mixing the natural flake graphite and potassium permanganate and heating them to 73-75° C., and then adding concentrated sulfuric acid and an activator; the present invention has no special requirements for the order of adding the concentrated sulfuric acid and the activator, as long as they can be added immediately when the system temperature is reached.
[0038] In the present invention, the temperature of the oxidative intercalation reaction is preferably 75-80°C, the reaction time is preferably 10-60 min, and more preferably 20-40 min; the oxidative intercalation reaction is preferably carried out under stirring conditions, and the stirring speed is preferably 250-350 r / min, and more preferably 290-330 r / min; in a specific embodiment of the present invention, it is preferred to start stirring immediately after adding concentrated sulfuric acid and an activator.
[0039] The present invention controls the temperature and rotation speed of the system to allow the natural flake graphite to undergo a full oxidation intercalation process. Potassium permanganate is used as an oxidant to oxidize and open the graphite flakes. At the same time, the swelling effect of the activator helps the graphite flakes to open more fully. More intercalation agent sulfuric acid is inserted into the graphite flakes to form graphite intercalation compounds. After the reaction is completed, the system is a brown slurry.
[0040] In the present invention, after the oxidation intercalation reaction, it is preferred that the obtained reaction solution is washed with water until the pH value is 3 to 7, preferably 6 to 7, and then filtered and dried to obtain the expandable graphite; the present invention removes excess activator, oxidant and other impurities by washing with water; the drying temperature is preferably 40 to 80°C, more preferably 50 to 70°C, and the drying time is preferably 2 to 5h; the present invention has a short drying time and low temperature, thereby reducing energy use; in a specific embodiment of the present invention, a silver-black powder is obtained after drying, which is the expandable graphite.
[0041] After obtaining expandable graphite, the present invention performs high-temperature expansion on the expandable graphite to obtain the high-expansion volume expanded graphite. In the present invention, the temperature of the high-temperature expansion is 800-900°C, preferably 890-900°C, and the time of the high-temperature expansion is preferably 3-5s. The present invention performs high-temperature expansion on the expandable graphite to obtain black worm-like expanded graphite. This process is to decompose the intercalation agent sulfuric acid at high temperature to produce gas, which produces impact force on the graphite sheet, thereby increasing the distance between the graphite layers to become expanded graphite. When phosphoric acid is used as an activator, the presence of phosphoric acid will generate polyphosphates to protect the graphite carbon layer at high temperature. It is well known that carbon will also be lost at high temperature, resulting in holes on the carbon layer. This change of phosphoric acid just makes up for the holes caused by carbon loss, increases the impact force of sulfuric acid decomposition on the graphite sheet, and the aforementioned more intercalation agents are inserted into the graphite sheet, so the expanded graphite with significantly increased expansion volume is obtained. In the present invention, the average expansion volume of the high-expansion volume expanded graphite obtained by the activation method reaches 400mL / g.
[0042] The present invention also provides a method for preparing high expansion volume expanded graphite by pretreatment (referred to as pretreatment method), comprising the following steps:
[0043] The natural flake graphite is immersed in a pretreatment agent for pretreatment to obtain pretreated natural flake graphite; the pretreatment agent is phosphoric acid, phosphate solution, hot water or an organic solvent; the temperature of the hot water is 60 to 90° C.; the organic solvent is a carboxylic acid or an alcohol;
[0044] The pretreated natural flake graphite, potassium permanganate and concentrated sulfuric acid are mixed to perform an oxidative intercalation reaction to obtain expandable graphite;
[0045] The expandable graphite is expanded at high temperature to obtain the high expansion volume expanded graphite; the temperature of the high temperature expansion is 800-900°C.
[0046] The present invention soaks natural flake graphite in a pretreatment agent for pretreatment to obtain pretreated natural flake graphite. In the present invention, the pretreatment agent is phosphoric acid, a phosphate solution, hot water or an organic solvent; the concentration of the phosphoric acid is preferably 83-88wt%, more preferably 85wt%; the concentration of the phosphate solution is preferably 0.375-0.425g / mL, more preferably 0.4g / mL; the phosphate is preferably dihydrogen phosphate, more preferably sodium dihydrogen phosphate; the organic solvent is a carboxylic acid or an alcohol; the carboxylic acid is preferably formic acid and / or acetic acid; the alcohol is preferably ethanol; the temperature of the hot water is preferably 60-90°C, specifically 60°C, 70°C, 80°C or 90°C; in a specific embodiment of the present invention, the pretreatment agent is most preferably hot water, which is cheap and easy to handle, and the effect of increasing the volume of the obtained expanded graphite is more obvious as the temperature of the hot water increases.
[0047] In the present invention, the pretreatment time is preferably 1 to 4 hours, more preferably 1 hour, 2 hours or 3 hours; when phosphoric acid, phosphate solution or organic solvent is used as the pretreatment agent, the pretreatment can be carried out at room temperature or under the condition of heating and stirring, and the effect is better when heating and stirring are used; the heating temperature is preferably 50 to 70°C, and the stirring speed is preferably 250 to 350 r / min, more preferably 290 to 330 r / min; the present invention has no special requirements for the amount of the pretreatment agent, and the natural flake graphite can be completely immersed. After the pretreatment is completed, the present invention preferably performs solid-liquid separation, and the obtained solid is the pretreated natural flake graphite; the present invention preferably recycles the liquid obtained by solid-liquid separation. The present invention uses a pretreatment agent to pretreat natural flake graphite, which can play a role in swelling the graphite flakes, reduce the amount of oxidant and intercalation agent in subsequent oxidation intercalation, and reduce the reaction time; at the same time, the pretreatment agent can be recycled and reused, saving the cost of the entire preparation process.
[0048] After obtaining the pretreated natural flake graphite, the present invention mixes the pretreated natural flake graphite, potassium permanganate and concentrated sulfuric acid to perform an oxidative intercalation reaction to obtain expandable graphite. In the present invention, the mass ratio of the natural flake graphite and potassium permanganate is preferably 1: (0.03-0.1), more preferably 1: 0.04, 1: 0.06 or 1: 0.08; the amount ratio of the natural flake graphite and concentrated sulfuric acid is preferably 1g: (1.5-4) mL, more preferably 1g: 1.5 mL, 1g: 2 mL or 1g: 3 mL; the concentration of the concentrated sulfuric acid is specifically 98wt%.
[0049] In the present invention, the mixing of pretreated natural flake graphite, potassium permanganate and concentrated sulfuric acid preferably comprises: firstly mixing natural flake graphite and potassium permanganate and heating them to 73-75° C., and then adding concentrated sulfuric acid.
[0050] In the present invention, the temperature of the oxidative intercalation reaction is preferably 75-80°C, the reaction time is preferably 10-40 min, and more preferably 10-30 min; the oxidative intercalation reaction is preferably carried out under stirring conditions, and the stirring speed is preferably 250-350 r / min, and more preferably 290-330 r / min; in a specific embodiment of the present invention, it is preferred to start stirring immediately after adding concentrated sulfuric acid.
[0051] The present invention slightly opens the graphite flakes through the swelling effect of the pretreatment agent, which can reduce the use of oxidants and intercalation agents, reduce costs and reduce environmental pollution. Alternatively, under the same oxidant and intercalation agent dosage conditions, pretreatment is first performed to allow more intercalation agents to enter the graphite flakes, and then the natural flake graphite is fully oxidized and intercalated by controlling the system temperature and rotation speed to form graphite intercalation compounds. After the reaction is completed, the system is a brown slurry.
[0052] In the present invention, after the oxidation intercalation reaction, it is preferred that the obtained reaction solution is washed with water until the pH value is 3 to 7, preferably 6 to 7, and then filtered and dried to obtain the expandable graphite; the drying temperature is 40 to 80°C, more preferably 50 to 70°C, and the drying time is preferably 2 to 5 hours, more preferably 3 to 4 hours.
[0053] After the expandable graphite is obtained, the present invention performs high-temperature expansion on the expandable graphite to obtain the high-expansion volume expanded graphite. In the present invention, the temperature of the high-temperature expansion is 800-900°C, preferably 890-900°C, and the time of the high-temperature expansion is preferably 3-5s; in the present invention, the expandable graphite is subjected to high-temperature expansion to obtain black worm-like expanded graphite. This process is to decompose the intercalation agent sulfuric acid at high temperature to produce gas, which produces impact force on the graphite sheet, thereby increasing the distance between the graphite layers to become expanded graphite. Because the graphite sheet is slightly opened due to pretreatment, more intercalation agents will enter the graphite sheet under the same conditions, so more intercalation agents will be gasified by high-temperature decomposition, and expanded graphite with significantly increased expansion volume is obtained.
[0054] In the present invention, the average expansion volume of the high expansion volume expanded graphite prepared by the pretreatment method reaches 450 mL / g; at the same time, compared with the aforementioned activation method, the pretreatment method has lower cost, is green and environmentally friendly, and has a more significant expansion effect.
[0055] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] Comparative Example 1
[0057] Weigh 2g natural flake graphite and 0.2g potassium permanganate into a beaker in a water bath, turn on the heating power supply, and when the temperature reaches 73°C, add 8mL 98wt% concentrated sulfuric acid to the system, turn on the magnetic stirring at 300r / min, react for 30min, and control the temperature during the reaction at 75°C. After the reaction, pour the mixed system into deionized water for washing until the pH is 6-7, filter, and dry at 60°C for 3h to obtain expandable graphite. Take 0.1g expandable graphite, expand it at high temperature for 3s in a muffle furnace at 900°C to obtain expanded graphite, put it into a measuring cylinder to measure its volume, and calculate the expansion volume of the expanded graphite.
[0058] Example 1
[0059] Expanded graphite was prepared according to the method of Comparative Example 1, except that after adding concentrated sulfuric acid to the system, 1 mL of 85 wt % phosphoric acid was immediately added.
[0060] Example 2
[0061] Expanded graphite was prepared according to the method of Comparative Example 1, except that after adding concentrated sulfuric acid to the system, 2 mL of 85 wt % phosphoric acid was immediately added.
[0062] Example 3
[0063] Expanded graphite was prepared according to the method of Comparative Example 1, except that after adding concentrated sulfuric acid to the system, 3 mL of 85 wt % phosphoric acid was immediately added.
[0064] Example 4
[0065] Expanded graphite was prepared according to the method of Comparative Example 1, except that after adding concentrated sulfuric acid to the system, 4 mL of 85% phosphoric acid was immediately added.
[0066] Example 5
[0067] Expanded graphite was prepared according to the method of Comparative Example 1, except that 2 g of sodium dihydrogen phosphate was immediately added to the system after concentrated sulfuric acid was added.
[0068] Example 6
[0069] Expanded graphite was prepared according to the method of Comparative Example 1, except that 4 g of sodium dihydrogen phosphate was immediately added to the system after concentrated sulfuric acid was added.
[0070] Example 7
[0071] Expanded graphite was prepared according to the method of Comparative Example 1, except that 6 g of sodium dihydrogen phosphate was immediately added to the system after concentrated sulfuric acid was added.
[0072] Example 8
[0073] Expanded graphite was prepared according to the method of Comparative Example 1, except that 8 g of sodium dihydrogen phosphate was immediately added to the system after concentrated sulfuric acid was added.
[0074] Example 9
[0075] Expanded graphite was prepared according to the method of Comparative Example 1, except that, before the reaction, natural flake graphite was soaked in 4 mL of 85 wt % phosphoric acid, and magnetic stirring was turned on at 290 r / min during the soaking process, and the soaking time was 1 h.
[0076] Example 10
[0077] Expanded graphite was prepared according to the method of Example 9, except that the oxidation intercalation reaction time was 10 min, that is, the oxidant and the intercalation agent were added to the system, and the magnetic stirring was turned on and the reaction was carried out for 10 min.
[0078] Embodiment 11
[0079] Expanded graphite was prepared according to the method of Example 9, except that the oxidation intercalation reaction time was 20 min, that is, the oxidant intercalant was added to the system, and the magnetic stirring was turned on and the reaction was carried out for 20 min.
[0080] Example 12
[0081] Expanded graphite was prepared according to the method of Example 9, except that the oxidation intercalation reaction time was 40 min, that is, the oxidant intercalant was added to the system, and the magnetic stirring was turned on and the reaction was carried out for 40 min.
[0082] Example 13
[0083] Expanded graphite was prepared according to the method of Example 10, except that the ratio of natural flake graphite and concentrated sulfuric acid was C (g): H2SO4 (mL) = 1:3, specifically, 6 mL of 98% concentrated sulfuric acid was added to 2 g of natural flake graphite and 0.2 g of potassium permanganate to obtain a mixed system.
[0084] Embodiment 14
[0085] Expanded graphite was prepared according to the method of Example 10, except that the ratio of natural flake graphite and concentrated sulfuric acid was C (g): H2SO4 (mL) = 1:2.
[0086] Embodiment 15
[0087] Expanded graphite was prepared according to the method of Example 10, except that the ratio of natural flake graphite to concentrated sulfuric acid was C (g): H2SO4 (mL) = 1:1.5.
[0088] Example 16
[0089] Expanded graphite was prepared according to the method of Example 10, except that the ratio of natural flake graphite to potassium permanganate was C(g):KMnO4(g)=1:0.08, that is, 0.16 g of potassium permanganate was weighed and put into a beaker for reaction.
[0090] Embodiment 17
[0091] Expanded graphite was prepared according to the method of Example 10, except that the ratio of natural flake graphite to potassium permanganate was C(g):KMnO4(g)=1:0.06.
[0092] Embodiment 18
[0093] Expanded graphite was prepared according to the method of Example 10, except that the ratio of natural flake graphite to potassium permanganate was C(g):KMnO4(g)=1:0.04.
[0094] Embodiment 19
[0095] Expanded graphite was prepared according to the method of Comparative Example 1, except that, before the reaction, natural flake graphite was soaked in 60° C. hot water, and magnetic stirring was turned on at 290 r / min during the soaking process, and the soaking time was 1 h.
[0096] Embodiment 20
[0097] Expanded graphite was prepared according to the method of Comparative Example 1, except that, before the reaction, natural flake graphite was soaked in 75° C. hot water, and magnetic stirring was turned on at 290 r / min during the soaking process, and the soaking time was 1 h.
[0098] Embodiment 21
[0099] Expanded graphite was prepared according to the method of Comparative Example 1, except that, before the reaction, natural flake graphite was soaked in 90° C. hot water, and magnetic stirring was turned on at 290 r / min during the soaking process, and the soaking time was 1 h.
[0100] Embodiment 22
[0101] Expanded graphite was prepared according to the method of Comparative Example 1, except that, before the reaction, natural flake graphite was soaked in 20 mL of sodium dihydrogen phosphate solution (0.4 g / mL), and magnetic stirring was turned on at 290 r / min during the soaking process, and the soaking time was 1 h.
[0102] Embodiment 23
[0103] Expanded graphite was prepared according to the method of Comparative Example 1, except that, before the reaction, natural flake graphite was soaked in 10 mL of formic acid, and magnetic stirring was turned on at 290 r / min during the soaking process, and the soaking time was 1 h.
[0104] Comparative Example 2
[0105] Commercially available expanded graphite is used as Comparative Example 2.
[0106] Test Case
[0107] 1. Characterization and morphology testing
[0108] Figure 1 The XRD patterns of the commercially available expanded graphite in Comparative Examples 1 and 2 are shown in Table 1. Figure 1 It can be seen that the (002) diffraction peak of graphite appears at 26.6°, and the (004) diffraction peak of graphite appears at 54.4°, indicating that the homemade expanded graphite has no impurities and no difference in crystal structure compared with the commercially available expanded graphite.
[0109] Figure 2 This is a SEM image of the expanded graphite prepared in Comparative Example 1. Figure 2 It can be seen that compared with the commercially available expanded graphite ( Figure 5 ), most of the graphite flakes have expanded, the worm-like structure is more obvious, the graphite flake structure is more fluffy, and the expanded volume is larger.
[0110] Figure 3 This is a SEM image of the expanded graphite prepared in Example 3. Figure 3 It can be seen that compared with Comparative Example 1, the expanded volume of the expanded graphite obtained in Example 3 is larger.
[0111] Figure 4 This is a SEM image of the expanded graphite prepared in Example 10. Figure 4 It can be seen that compared with Comparative Example 1 and Example 3, the expanded volume of the expanded graphite obtained in Example 10 is larger.
[0112] Figure 5 This is a SEM image of commercially available expanded graphite. Figure 5 It can be seen that the expansion volume of commercially available expanded graphite is smaller.
[0113] 2. Expansion volume test
[0114] The expansion volumes of the expanded graphites in Comparative Example 1 and Examples 1 to 23 were obtained by weighing and calculating, and the results are listed in Table 1.
[0115] Table 1 Expansion volume of expanded graphite in comparative example 1 and examples 1 to 23 and expansion volume values of comparative examples
[0116]
[0117]
[0118] As can be seen from Table 1, by adding phosphoric acid as an activator, the expansion volume of expanded graphite can be significantly increased. According to Examples 1 to 4, it can be seen that as the phosphoric acid content in the system increases, the expansion volume first increases and then decreases. The main reason is that the presence of phosphoric acid makes the graphite lamellae open more fully, more intercalation agents enter the graphite lamellae, and the intercalation agents that decompose and gasify during subsequent high-temperature expansion are more, and the impact force on the carbon layer is greater, and the expansion volume is also greater; but when the phosphoric acid content continues to increase, it will cause the oxidant concentration to decrease, the oxidation ability of the graphite lamellae is weakened, the degree of opening of the lamellae is reduced, and the amount of intercalation agents entering is also reduced, so the expansion volume is reduced. When the amount ratio of natural flake graphite and phosphoric acid is 1g:1.5mL, the expansion volume of the obtained expanded graphite reaches 450mL / g, which is 90mL / g higher than Comparative Example 1. In order to explore whether the cause of the phosphoric acid effect is hydrogen ions or phosphate, the phosphoric acid in the system is replaced with an equal amount of sodium dihydrogen phosphate. According to Examples 5 to 8, it can be seen that when the phosphate content in the system is the same, the volume of the expanded graphite is the same, indicating that the activation process is caused by phosphate.
[0119] It can be seen from the data in Table 1 that by using phosphoric acid as a pretreatment agent, first soaking and treating natural flake graphite, and then performing subsequent oxidation intercalation reaction, expanded graphite with a larger expansion volume can be prepared. Importantly, compared with Comparative Example 1, this preparation method can shorten the reaction time, reduce the amount of oxidant intercalation agent, and at the same time, the expansion effect is better, and the pretreatment solvent used can also be recycled and reused. According to Examples 9 to 12, when the amount of oxidant and intercalation agent is the same, the reaction time can be shortened by pretreatment. According to Examples 13 to 18, after reducing the amount of oxidant and intercalation agent, the expansion volume of the obtained expanded graphite is equivalent to or higher than that of Comparative Example 1, indicating that pretreatment can reduce the amount of oxidant and intercalation agent.
[0120] It can be seen from the data in Examples 19 to 21 in Table 1 that by replacing phosphoric acid with a swelling effect with hot water at different temperatures, expanded graphite with a significantly increased expansion volume can also be prepared. This preparation method is low in cost, green and environmentally friendly, and has significant effects.
[0121] It can be seen from the data of Examples 22 to 23 in Table 1 that by using phosphate solution and formic acid as pretreatment agents, expanded graphite with significantly increased expansion volume can also be obtained.
[0122] In summary, it can be found from Table 1 that the expansion volume of the expanded graphite prepared by the activation method or the pretreatment method of the present invention is much higher than that of the expanded graphite prepared by the traditional method and commercially available.
[0123] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing high expansion volume expanded graphite by activation, characterized in that, The following steps are involved: Natural flake graphite, potassium permanganate, concentrated sulfuric acid and an activator are mixed to perform an oxidation intercalation reaction to obtain expandable graphite; the activator is phosphoric acid, phosphate or an organic solvent; the organic solvent is one or more of carboxylic acid and alcohol; The expandable graphite is expanded at high temperature to obtain the high expansion volume expanded graphite; the temperature of the high temperature expansion is 800-900°C.
2. The method according to claim 1, characterized in that The mass ratio of the natural flake graphite to potassium permanganate is 1:(0.08-0.4); the dosage ratio of the natural flake graphite to concentrated sulfuric acid is 1g:(2-6)mL; when the activator is phosphoric acid or an organic solvent, the dosage ratio of the natural flake graphite to the activator is 1g:(0.5-2)mL; when the activator is phosphate, the mass ratio of the natural flake graphite to the activator is 1:(1-4); the concentration of the phosphoric acid is 83-88wt%; the carboxylic acid is formic acid and / or acetic acid; the alcohol is ethanol; and the phosphate is dihydrogen phosphate.
3. The method according to claim 1, characterized in that The mixing of natural flake graphite, potassium permanganate, concentrated sulfuric acid and an activator comprises: firstly mixing the natural flake graphite and potassium permanganate and heating them to 73-75° C., and then adding concentrated sulfuric acid and an activator; The temperature of the oxidation intercalation reaction is 75-80° C., and the reaction time is 10-60 minutes.
4. The method according to claim 1, characterized in that: After the oxidation intercalation reaction, the obtained reaction solution is washed with water until the pH value is 3-7, and then filtered and dried to obtain the expandable graphite; the drying temperature is 40-80°C and the time is 2-5 hours.
5. The method according to claim 1, characterized in that The high temperature expansion time is 3 to 5 seconds.
6. A method for preparing high expansion volume expanded graphite by pretreatment, characterized in that, The following steps are involved: The natural flake graphite is immersed in a pretreatment agent for pretreatment to obtain pretreated natural flake graphite; the pretreatment agent is phosphoric acid, phosphate solution, hot water or an organic solvent; the temperature of the hot water is 60 to 90° C.; the organic solvent is a carboxylic acid or an alcohol; The pretreated natural flake graphite, potassium permanganate and concentrated sulfuric acid are mixed to perform an oxidative intercalation reaction to obtain expandable graphite; The expandable graphite is expanded at high temperature to obtain the high expansion volume expanded graphite; the temperature of the high temperature expansion is 800-900°C.
7. The method according to claim 6, characterized in that The pretreatment time is 1 to 4 hours.
8. The method according to claim 6, characterized in that The mass ratio of the natural flake graphite to potassium permanganate is 1:(0.03-0.1); the dosage ratio of the natural flake graphite to concentrated sulfuric acid is 1g:(1.5-4)mL; The concentration of the phosphoric acid is 83-88 wt %; the concentration of the phosphate solution is 0.375-0.425 g / mL; the carboxylic acid is formic acid and / or acetic acid; the alcohol is ethanol; and the phosphate is dihydrogen phosphate.
9. The method according to claim 6, characterized in that After the oxidation intercalation reaction, the obtained reaction solution is washed with water until the pH value is 3-7, and then filtered and dried to obtain the expandable graphite; the drying temperature is 40-80°C and the time is 2-5 hours.
10. The method according to claim 6, characterized in that The high temperature expansion time is 3 to 5 seconds.
Citation Information
Patent Citations
Preparation method of expandable graphite
CN103663443A
Preparation method of material of negative electrode of lithium ion battery
CN104993174A
Preparation method of sulfur-free expansible graphite
CN105502360A
Method for preparing highly-expandable low-sulfur graphite intercalation compound
CN106629703A
Preparation of expandable graphite at low-temperature
CN1613757A
Cited By
Preparation method of expansible graphite with high expansion rate
CN117023576A